Southern and southeastern boundaries: A geometric morphometric analysis of bifacial points from Minas Gerais, São Paulo, Paraná, and Rio Grande do Sul (Brazil) [Fronteiras sul e sudeste: Uma análise morfométrica de pontas bifaciais de Minas Gerais, São Paulo, Paraná e Rio Grande do Sul (Brasil)] - Okumura, Mercedes; Araujo, Astolfo G. M. (Journal of Lithic Studies, 2017)
Style and function in archaeological or ethnographic artifacts have been studied by a myriad of researchers through the most diverse theoretical approaches. In this context, the study of projectile points has been particularly useful in generating a greater knowledge of these artifacts as markers of identity, reflecting potential boundaries between groups. This work aims at exploring the differences in the morphology of Holocene bifacial points from Minas Gerais, São Paulo, Paraná and Rio Grande do Sul in light of the concepts of style and function set out by evolutionary archaeology. In this study, 248 points were analyzed by two dimensional geometric morphometrics. Although the analysis involves geometric morphometrics data of the complete point, the shape of the stem was considered to be of particular importance. According to the theoretical expectations and the heuristic models of style and function proposed by Dunnell (1978a), differences in the shape of the stem of the points can be considered a stylistic resource whose aspect and differential replication among groups was most likely due to stochastic processes. Thus, the theoretical expectation in this study is that the shape of the stem reflects the choices of the groups and, ultimately, is a reflection of potential ancient cultural boundaries. The results point to the presence of important differences in the size and general shape of the points from Minas Gerais, São Paulo, and Paraná in relation to the points from Rio Grande do Sul. These differences can also be observed in the stem morphology, showing the benefit of the application of the heuristic dichotomy between style and function (sensu Dunnell 1978a) to better understand the presence of potential past cultural boundaries.